Biocompatibility of N-(2-hydroxypropyl) methacrylamide copolymers containing adriamycin. Immunogenicity, and effect on haematopoietic stem cells in bone marrow in vivo and mouse splenocytes and human peripheral blood lymphocytes in vitro - Rihova, B; Bilej, M; Vetvicka, V; Ulbrich, K; Strohalm, J; Kopecek, J; Duncan, R (Biomaterials, 1989)
N-(2-hydroxypropyl)methacrylamide polymeric prodrugs containing adriamycin bound to polymers via glycylphenylalanylleucylglycine side chains and, in one case, galactosamine bound via the same sequence, were tested for immunogenicity after intravenous, subcutaneous and oral application in two inbred strains of mice. The serum antibody level was determined by enzyme-linked immunoassay on the 3rd and 6th day after the last treatment. It was found that antibodies were only produced in very small amounts. In some experimental groups, the antibody titres measured following administration of copolymer conjugate were comparable with those present in non-treated controls. Attachment of adriamycin to N-(2-hydroxypropyl)methacrylamide copolymer considerably decreased its toxicity against haematopoietic precursors in bone marrow as measured by the in vivo colony-forming unit-spleen assay and its ability to inhibit [3H] thymidine incorporation by mouse splenocytes and human peripheral blood lymphocytes measured in vitro.
Keywords: Polymethacrylic Acids; doxorubicin; Male; slezina; techniky in vitro; mužské pohlaví; lymfocyty; hematopoetické kmenové buňky; Spleen; Animals; lidé; biokompatibilní materiály; kyseliny polymethakrylové; ženské pohlaví; Humans; Lymphocytes; zvířata; tvorba protilátek; myši; inbrední kmeny myší; Antibody Formation; Hematopoietic Stem Cells; Mice; Female; Mice, Inbred Strains; Biocompatible Materials; Doxorubicin; In Vitro Techniques